Análise por injeção em fluxo para determinação da capacidade antioxidante total de vinhos utilizando o método DPPH : otimização das condições a partir metodologia de superfície de resposta - Bukman, Lais (2012)
Antioxidants are substances that react with free radicals stabilizing and preventing their harmful actions to the organism and are present in a wide variety of foods and beverages. Due to importance of antioxidant activity in the some foods, several analytical methods have been proposed among them include FRAP, ORAC, total polyphenol content and DPPH methods. The main objective of this study is to propose an analytical methodology using a flow injection analysis system (FIA), with a merging zones configuration, for determination of total antioxidant activity by DPPH radical scavenging assay. The FIA system conditions were optimized with the response surface methodology using the central composite rotatable design. The optimization parameters studied were: the carrier flow rate, the lengths of the sample and reagent loops and the length of the reactor. According to the results, levels of selected parameters were: carrier flow rate 1.12 mL min-1, length of the loops 18.5 cm and length of the reactor 234.6 cm. The detection and quantification limits were, respectively, 2.647 and 8.824 μ mol L-1 acid galic / mL wine. The proposed method had an analytical frequency of 41 samples per hour and a 58% saving in the consumption of reagent DPPH and 62.6% in the consumption of carrier agent methanol compared to the conventional method. The DPPH assay adapted to the FIA system under the optimization conditions was utilized to determine the antioxidant activity of wine samples.